Aplicación del proceso de atención de enfermería a una paciente de 35 años de edad hospitalizada en el área de ginecología por Bartolinitis, en el Hospital General Guasmo Sur. - Durango Almeida, Johanna Lisbeth (2019)
In the present case study, we will talk about a 35-year-old patient who developed bartolinitis or bartholin gland abscess, during her admission to the emergency area, she presented a clinical picture of approximately 3 days of evolution characterized by severe pain right inner thigh insertion level, more mass. Before coming, he went to the nearest health center where they value and give medication (Diclofenac, ceftriaxone, Ciprofloxacin) The patient, who informs us that this lesion has been presenting it for 7 days, is again questioned, in addition to presenting non-quantified thermal rise and chills. A patient is reassessed with laboratory results showing a leukocytosis with neutrophilia. The patient is told about her pathology, in addition to the measures to be followed. Second antibiotic is added to your treatment plus analgesia and gastric protector. Return for swelling edema and erythema and heat at the level of the right major lip. She is admitted to the gynecology room of the IESS (Babahoyo), during her hospital stay she developed severe pain in the genital region due to an increase in the volume of the right major lip. Therefore, she underwent surgery for abscess of the right Bartholin gland. Draining purulent content too foul, blackish color, performing a marsupialization to empty all the content and result in a bag similar to the marsupials. Healing with saline was performed during his recovery, no pain was manifested, antibiotic treatment was proposed, it was decided not to discharge until 7 days with antibiotic treatment. On the 5th post-surgical marsupialization day. A medical discharge is made, talks are given about the care that should be taken in the vulva.